Patch Testing with Dental Screening Series in Oral Disease - Kim, Tae-Wook (Ann Dermatol, 2015)
BACKGROUND: The oral mucosa is constantly exposed to several irritants and allergens including dental materials, but the role of contact allergy in oral disease is obscure. OBJECTIVE: To analyze positive patch test results in patients with oral diseases and evaluate the clinical relevance of oral diseases with contact allergy to dental materials. METHODS: We retrospectively analyzed patch test results with dental screening series in 44 patients with oral disease from 2004~2011. RESULTS: Oral diseases included oral lichen planus (54.5%), cheilitis (27.3%), burning mouth syndrome (9.1%), and others (9.1%). Thirty-one of 44 patients (70.5%) had positive reactions to one or more allergens. The most commonly detected allergens were gold sodium thiosulfate (25.0%) and nickel sulfate (25.0%), followed by potassium dichromate (22.7%), cobalt (15.9%), palladium (6.8%), mercury (4.5%), copper (4.5%), and methylhydroquinone (4.5%). Six of 24 patients with oral lichen planus had a symptom in areas adjacent to dental materials and positive patch test reactions to allergens contained in the suspected dental materials. CONCLUSION: Patch tests with dental screening series are worth considering for oral diseases, especially for oral lichen planus.